2017
DOI: 10.1027/0227-5910/a000460
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Suicide Crisis Services to Text and Chat

Abstract: While new platforms offer promise, participants also indicated that chat services can supplement phone lines, but not replace them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 15 publications
1
37
0
Order By: Relevance
“…As a whole, it is clear that this specific crisis line centre deals largely with calls in which callers are reporting current or past adult and child violence. Consistent with the centre's broader focus, it also ap- As previously discussed, crisis line centres are often the first contact for individuals reaching out for mental health-related services (Predmore et al, 2017). Rarely, though, has research focused on characterising the victimisation histories reported by callers, as we have done in the current study.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…As a whole, it is clear that this specific crisis line centre deals largely with calls in which callers are reporting current or past adult and child violence. Consistent with the centre's broader focus, it also ap- As previously discussed, crisis line centres are often the first contact for individuals reaching out for mental health-related services (Predmore et al, 2017). Rarely, though, has research focused on characterising the victimisation histories reported by callers, as we have done in the current study.…”
Section: Discussionsupporting
confidence: 61%
“…Research suggests that crisis lines are the first contact with mental health-related services for many people (e.g. Predmore et al, 2017), making them an especially important community and public health intervention. Given the vast current and potential utility of crisis lines, characterising the current trends and utilisation of these services is crucial to identifying targeted ways to improve such services.…”
Section: Introductionmentioning
confidence: 99%
“…Telephone crisis services (sometimes called 'hotlines') constitute a further example of an indicated intervention 246 . These services have existed since the 1950s 247 , and many have now embraced newer technology like online chat and text-messaging services 248 .…”
Section: [H2] Assessment and Determination Of Riskmentioning
confidence: 99%
“…We were not able to use a natural language processing program viable for this analysis in the Polish language. However, we hope that future analysis of medical forum content may be enhanced by the application of natural language processing methods [35]. Finally, the study does not provide the characteristics of the users.…”
Section: Limitationsmentioning
confidence: 98%
“…Currently, there are many efforts to provide online interventions to individuals who present suicidal behaviour on the Internet [33,34]. For instance, the crisis support service for people with suicidal thoughts in the US is provided via both phone hotline and anonymous chat [35]. Similarly, it is worth considering informing the community about alarm symptoms as well as working up similar online interventions for individuals who search for information related to these symptoms.…”
Section: Main Findingsmentioning
confidence: 99%